Adolescents and substance use 3: treatment - James, Philip (Institute of Guidance Counsellors, Ireland, 2025)
This is the final article in a series of three which have examined the issue of adolescent substance use. The first article gave an overview of the different substances that are frequently used by adolescents while the second article provided an overview of prevention approaches. This article focuses on the issue of treatment for those who are using substances. It gives an insight into what substance use treatment is, when someone ought to be referred for it, how it can be accessed, as well as an overview of different treatment approaches.
PUBLISHED